Impact of Independent Commissioner Proportion and Leverage on Financial Performance of Indonesian Consumer Non-Cyclicals - Yudiska, Sonia; Rosalina, Erita; Yanto, Yanto (Riset Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study examines the effect of independent commissioner proportion and leverage on the financial performance of consumer non-cyclicals companies listed on the Indonesia Stock Exchange during 2020–2024. In this study, financial performance is measured using ROE. Methodology: This study employs a quantitative approach using secondary data from the annual financial reports of 20 companies selected through purposive sampling. Data analysis was performed using panel data regression techniques with EViews 12 software to examine the effects of the independent variables on financial performance. Results: The findings show that leverage has a negative and significant effect on ROE, indicated by prob (0.0001). Meanwhile, the percentage of independent commissioners has no significant relationship, as shown by prob (0.8454). Conclusions: This study concludes that leverage is an important factor affecting financial performance, while the proportion of independent commissioners has no significant influence on ROE. Limitations: This study is limited to consumer non-cyclicals companies listed on the IDX and only examines two independent variables during the 2020–2024 period. Contribution: This study provides empirical information about the factors influencing financial performance and contributes to the development of corporate governance and financial management literature in Indonesia.